Cycle of Violence in Schools: Longitudinal Reciprocal Relationship Between Student’s Aggression and Teacher’s Use of Corporal Punishment - Choi, Boungho (Journal of interpersonal violence, 2021)
The purpose of this study is to examine the longitudinal reciprocal relationship between student’s aggression and teacher’s use of corporal punishment. An autoregressive cross-lagged model was analyzed with the data drawn from 4,051 Korean secondary students (male = 2,084, female = 1,967), in Gyeonggi Education Panel Study for three waves (seventh-ninth grades). Results revealed that student’s aggression provoke teacher’s use of corporal punishment and also teacher’s use of corporal punishment provokes student’s aggression. It is important in that it suggests the cycle of violence with the reciprocal relationship between student’s aggression and teacher’s use of corporal punishment, rather than positing the unidirectional effects. Practically, teachers should keep in mind that corporal punishments, which are at least partially attributable to student’s aggression, actually worsen the problem and lead to a cycle of violence in schools. Accordingly, they should instead respond with alternative disciplinary strategies or direct interventions dealing with the causes of aggression.